1984
DOI: 10.1507/endocrj1954.31.291
|View full text |Cite
|
Sign up to set email alerts
|

Food constituents as a cause of variation of C-peptide excretion in the urine.

Abstract: Since C-peptide immunoreactivity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In the NIDDM subjects in our study, this figure was 14.8%. Takai et al (17) studied the reproducibility of the 24-h urinary excretion of C-peptide in 10 normal and 17 NIDDM subjects (17). The coefficient of variation of urinary C-peptide was 23.4% in the normal and 39.1% in the diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…In the NIDDM subjects in our study, this figure was 14.8%. Takai et al (17) studied the reproducibility of the 24-h urinary excretion of C-peptide in 10 normal and 17 NIDDM subjects (17). The coefficient of variation of urinary C-peptide was 23.4% in the normal and 39.1% in the diabetic subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The reproducibilities of these two tests have not been evaluated in insulin dependent diabetic patients. Though they studied non-insulin dependent diabetic patients, Takai et al 18 ) found that the consecutive measurement of 24-h urinary C-peptide (ug/day) revealed a considerable day-to-day variation in 17 patients (the average coefficient of variation = 39.1%). They suggested that the variability could be ascribed to the change in diet, the effect of exercise, and the variable urinary clearance of C-peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of a meal including fat also permits the study of postmeal lipemia. Takai et al (34) and Hoogwerf et al (33) found that carbohydrate and protein but not fat led to additive acute increases in UCP. Clearly, studies with food as the stimulus to insulin secretion must address the need to standardize the mix of carbohydrate and protein to be used.…”
Section: Meal-stimulated Ucpmentioning
confidence: 99%